2014
DOI: 10.1159/000368553
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Air Pollution on Multiple Sclerosis in Tehran, Iran

Abstract: <b><i>Background:</i></b> Multiple sclerosis (MS) incidence has dramatically increased in Tehran, Iran. The health impact of air pollution in Tehran underscores the attention to a possible association to this environmental risk factor. In this study, the authors aimed to analyze the spatial distribution of prevalent MS cases and their association with the spatial patterns of air pollution. <b><i>Methods:</i></b> Patient records meeting McDonald's criteria for def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 26 publications
2
69
1
Order By: Relevance
“…Clustering pattern of MS prevalence patients were also observed in Tehran [109,110], and a significant difference in long term exposure to PM 10 , SO 2 , NO 2 , and NO x was observed in MS cases compared with controls [109]. A recent study in Tehran found higher relapse rate during the winter and following first month of the spring and MS relapses were correlated with NO levels [111].…”
Section: Air Pollution As a Risk Factor In Msmentioning
confidence: 96%
“…Clustering pattern of MS prevalence patients were also observed in Tehran [109,110], and a significant difference in long term exposure to PM 10 , SO 2 , NO 2 , and NO x was observed in MS cases compared with controls [109]. A recent study in Tehran found higher relapse rate during the winter and following first month of the spring and MS relapses were correlated with NO levels [111].…”
Section: Air Pollution As a Risk Factor In Msmentioning
confidence: 96%
“…Nonetheless, while there is mounting evidence that vitamin D exerts broad regulatory effects on cells of the adaptive and innate immune systems 2,3 , there is remarkably little evidence that treatment with vitamin D can influence MS evolution and prognosis 4,5,6,7 . So far, no clinical trial has provided any clear evidence that vitamin D alone can alter the course of an extremely complex disease like MS. Other vitamins 8,9,10 , genetic predisposition 11,12 and several environmental factors 13,14,15,16 may also play a substantial role in MS. However strong the role of vitamin D in the orchestra of factors associated with MS may be, this might be better seen in high-latitude countries.…”
mentioning
confidence: 99%
“…To our knowledge, the current study is the first to have looked at potential sources through industrial output and examine childhood exposure and MS risk. In other adult MS studies, increased exposure to larger particulate matter (PM 10 ) was related to both increased risk for MS in adults20, 23 and MS relapse using hospitalization records 18, 19, 24…”
Section: Discussionmentioning
confidence: 99%
“…Although some adult MS studies have suggested a relationship between air constituents and MS,18, 19, 20 not all of the Environmental Protection Agency (EPA) criteria air pollutants have been assessed, including fine PM 2.5 , ground level ozone precursors, and lead. Furthermore, the proximity of MS patients to industrial facilities that release toxic chemicals into the air has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%